Vietnam : 2004 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that the three-year Poverty Reduction and Growth Facility arrangement for Vietnam expired in April 2004. During the arrangement, Vietnam maintained strong economic growth and low inflation, and achieved further poverty reduction, supported by favorable macroeconomic conditions and increasing integration with the world economy facilitated by trade liberalization. For 2004 as a whole, economic growth and the external current account are likely to be broadly unchanged from 2003, with inflation falling toward the end of the year and the budget deficit narrowing.